Desenvolvimento de um produto bioinseticida à base de bacillus thuringiensis subsp. kurstaki HD-1 - Martins, Luciane Müller (2016)
In order to minimize the significant environmental impact consequent to the indiscriminate use of chemicals on crops, biopesticides have been proposed increasingly for pest control and integrated management. Despite the proven Bacillus thuringiensis efficiency in these products, there are still limitations to its use due to the cost of production and lack of knowledge regarding the correct utilization of the formulations. This study aimed at developing a biopesticide product based on Bacillus thuringiensis subsp. kurstaki HD-1, which attends the quality criteria and is viable industrially. Initially the influence of the culture medium composition on the growth and sporulation was evaluated. The modification in the nitrogen source, adding peptone to the yeast exteract present in the original medium, did not present significant effect. However the modification in the carbon source, from glucose to sucrose, resulted in significantly higher sporulation (4.83.108 UFC/mL) in agitated flasks. For the cultivation in 5 L bottles comparing glucose and sucrose, there was no difference between the maximum concentrations of spores obtained in both media, between 2.107 and 3.107 UFC/mL after 34 h, however, no consumption of sucrose by the microorganism was verified. In a bench-scale bioreactor (7.5 L) in batch mode using glucose as carbon source, the sporulation peak occured in 30 h (4.83.1010 UFC/mL). In fed-batch mode with glucose, using the same medium, the maximum value of sporulation was obtained after 72 h of cultivation (4.44.1012 UFC/mL). The presence of proteins with estimated molecular weights of 70 kDa and 130 kDa, charactertistic of the toxins of interest, was observed in electrophoresis gel, visually in higher concentration in the samples of the fedbatch process. A formulation was proposed for the concentrated broth of Bacillus thuringiensis subsp. kurstaki HD-1 produced in batch and fed-batch modes. The formulations were tested by bioassay with the lepidoptera Spodoptera frugiperda in order to verify the lethal concentration (LC50). The LC50 of the batch formulation was 635.121 spores/mL and the one of the fed-batch formulation was 10.994 spores/mL.